Integrasi Pasar dan Elastisitas Transmisi Harga Daging Ayam Ras (Broiler) di Pasar Tradisional Indonesia - Pratiwi, Dita; Andarwangi, Tunjung; Tantriadisti, Shinta; Ulfah, Maria (Universitas Galuh, 2025)
Broiler chicken meat is one of the highly sought-after food commodities in Indonesia. However, the price of broiler chicken meat at the consumer level tends to fluctuate. This indicates that issues within the distribution pattern of broiler chicken meat. The distribution pattern of broiler chicken meat is closely related to market integration. Therefore, a study is conducted to examine the market integration of broiler chicken meat at both the farmer and retailer levels. The data used in this study consists of monthly time series data spanning five years from January 2018 to December 2022. The study on the market integration of broiler chicken meat employs the analysis of the Index of Market Connection (IMC). Based on an IMC value of 0.4767 and β2 of 0.755, it can be concluded that the market integration of broiler chicken meat at the farmer and traditional market levels falls under strong long-term integration. The price transmission elasticity for broiler chicken meat in this study is 0.812, where ET < 1 indicates that the rate of change in the price of broiler chicken meat at the farmer level is smaller or slower than the rate of change in the price of broiler chicken meat at the retailer level in traditional markets. In other words, a 1% increase in price at the retailer level would only result in a 0.81% change in price at the farmer level. This suggests that the marketing system for broiler chicken meat in traditional markets in Indonesia is still considered inefficient.